INFLUENCE OF POPULATION GROWTH RATE, POPULATION DENSITY, SEX RATIO ON THE POOR POPULATION - Anjel Ezania Sihombing; Ajeng Ajeng Windi Astuti; Lutfiah Nur Azizah; Zakia Hasanah Hasibuan; Nazwa Fazirah Nasution (Universitas Negeri Medan, 2024)
In 2016–2022, this study examines how population growth rate, population density, and sex ratio affect poverty levels in five islands in Sumatra simultaneously and partially. where population density, sex ratio, and population growth rate act as independent variables while poverty functions as the dependent variable. Time series data is used in this study, and panel data analysis conducted with eViews is used to apply quantitative descriptive analysis techniques. The Central Bureau of Statistics (BPS) is the source of information. The findings of this study indicate that: 1) Population growth rate has a significant and positive impact on poverty. 2) Poverty is significantly and negatively affected by population density. 3) The relationship between sex ratio and poverty is quite positive. Keywords: poverty, sex ratio, population density, and population growth rate.